Effect of Bavistin and Adenine Sulphate on In vitro Shoot Multiplication of Picrorhiza scrophulariiflora (Plant Tissue Culture and Biotechnology, 2010)
An alternative protocol for in vitro propagation of Picrorhiza scrophulariiflora is described using bavistin and adenine sulphate. The explants differentiated into multiple shoot buds on MS supplemented with various concentrations of bavistin and adenine sulphate ranging from 0 - 400 mg/l either alone or in combination. Maximum number of multiple shoots were obtained on MS containing the combination of bavistin (100 mg/l) and adenine sulphate (100 mg/l). In this combination as high as 28 shoots per explant was achieved and also vetrification of the cultures were not recorded. This study also demonstrates that the bavistin has stronger cytokinin-like activity than adenine sulphate. For instance, it was observed that bavistin alone in the concentration of 300 mg/l produced as high as 24 shoots per explant, however, adenine sulphate (100 mg/l) could produce a maximum of 18 shoots per explant. Moreover, higher or lower concentration did not improve the shoot multiplication. The microshoots were separated from the multiple shoots and transferred to MS containing various concentrations of auxins. Among them, NAA (1 mg/l) produced as high as 6 roots per explant. The regenerated plantlets were hardened in plastic cups (6 x 8 cm) containing 9 : 1 virgin soil and soil at Kyongnosla nursery and acclimated for four weeks. A 90% survival rate of the plants was recorded after 60 days. D.O.I. 10.3329/ptcb.v19i2.5441 Plant Tissue Cult. & Biotech. 19(2): 237-245, 2009 (December)